Kebijakan Kesehatan di Indonesia: Tinjauan, Tantangan, dan Rekomendasi - Irfan Sazali Nasution; Nurhazizah Br Said; Mutiara Salsabila; Ayu Maulidia; Zahwa Sinta Aulia; Suci ramadhani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The Indonesian government has made various efforts to overcome this health problem, such as through the National Health Insurance (JKN) program which aims to provide more equitable access to health services for the entire population. This study aims to identify and analyze key health policies in Indonesia, as well as evaluate the successes and challenges in their implementation. The research method uses the literature review method to analyze, identify and analyze key health policies in Indonesia, as well as evaluate the successes and challenges in their implementation. The research method uses the literature review method to analyze, identify and analyze key health policies in Indonesia, as well as evaluate the successes and challenges in their implementation. Literature review is an effective method for collecting, analyzing, and synthesizing information from various sources relevant to the research topic. The results of the study show that the importance of health policies in Indonesia to improve public health. Through the identification of key health policies, evaluation of their successes, and challenges in their implementation, this study provides an in-depth understanding of the political dynamics that influence health policies. In conclusion, by identifying key health policies, evaluating their success, and facing challenges in their implementation, this study provides a comprehensive understanding of the political dynamics that influence health policies.